Factor Affecting Measles Rubella Immunization During Nation Child Immunization Month (BIAN) at Karya Wanita Public Health Center (Puskesmas Karya Wanita) Pekanbaru - Susanti, Lasiah (International Journal of Healthcare Research, 2023)
Background : Measles Rubella (MR) vaccine should be given to children aged 9 to 72 months. Indonesian Government held Bulan Imunisasi Anak Nasional (BIAN) to ensure every child accept MR vaccine. Throughout Indonesia, in Riau Province itself the proportion of MR vaccine rate was still relatively low, ranking 28th out of 34 provinces with a proportion of 68.9%. In Pekanbaru City, the MR vaccine reached 77.6%, where Indonesia national target is 95%. The Karya Wanita Public Health Center Pekanbaru is one of 5 Public Health Centers with low achievement in BIAN program, reaching only 36% MR vaccine rate. Low MR vaccine rate is possibly caused by several factors such as mother's knowledge, mother's attitude, mother's occupation, mother's education, and family support. Methods : In this research, the method used is quantitative with a cross sectional approach and purposive sampling technique. While the test used is the Spearman rank correlation test with a sample of 124. Results : Factors associated with maternal Measles Rubella (MR) immunization behavior during National Child Immunization Month (BIAN) were mothers education (p = 0.001), mothers occupation (p = 0.805), mothers knowledge level (p = 0.000), mothers attitude (p = 0.015), and family support (p = 0.000). Conclusion: It can be conclude that factors related to maternal Measles Rubella (MR) immunization behavior during National Child Immunization Month (BIAN) are mothers education, mother's level of knowledge, mother's attitude, and family support.